Fenomena Kepemilikan Tanah Tanpa Bersertifikat Oleh Masyarakat (Studi Kasus: Desa Concong Tengah Kecamatan Concong) - M. Asikin; Triyana Syahfitri; Ali Azhar (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
This study aims to analyze the phenomenon of unregistered land ownership among the community of Desa Concong Tengah, Kecamatan Concong, and to examine its legal force under positive law. This research employed an empirical legal research method (field research), using primary data obtained through direct interviews with the Village Head, Village Secretary, hamlet heads, and members of the community, supported by secondary data from statutory regulations, books, and journals. The data were analyzed qualitatively in a descriptive-analytical manner. The findings show that most land transactions in Desa Concong Tengah are carried out only at the sub-district or village level without registration at the National Land Agency (BPN), mainly because of the community's limited understanding of the importance of a land title certificate, the considerable distance to the BPN and PPAT offices, the absence of direct outreach from those institutions, and the registration costs that are difficult for the community to afford. From the perspective of positive law, particularly Government Regulation Number 24 of 1997 concerning Land Registration, unregistered land only provides weak evidentiary force compared to a Certificate of Ownership (Sertifikat Hak Milik), which under Article 32 serves as strong evidence of both physical and juridical data. Consequently, the community's legal protection over land acquired without a certificate remains vulnerable to disputes, and legal certainty can only be strengthened through land registration with the BPN.